Changing Face of Indian Political Cartoons from 2010–2020 - Singh, Ananya; Dada Ozarkar, Anantkumar (Indian Journal of Marketing, 2023)
Political cartoons are a reflection of the politics in the country and democracy as a whole. As time changed, media and politics changed, too. Therefore, it is important to understand how political cartoons are changing, especially when they are known to play a critical role in democracy. Comparison and analysis of political cartoons over time could bring about reasonable findings. The present research focused on mending this gap in the existing literature and analyzed the changing face of Indian political cartoons over the past decade. The present study was conducted on Editors of different editorials (English and Hindi) based in the Delhi-NCR region, India. Primary data were used in the study, wherein the interview method was adopted to collect the data in the form of interview transcripts. Herein, qualitative analysis was conducted wherein the interview method was adopted. The study’s findings threw light on how the face of political cartoons has changed over the past decade. The research findings could be used by practicing political cartoonists to update themselves. Further, the newspaper could also use this study to analyze how to keep the dying art of political cartooning alive. The research conducted on political cartooning is very limited, and the focus on changes in political cartooning is almost zero. Thus, the present research is one of its kind.